Comparing the Effects of Chinese and Traditional Official Finance on State Repression and Public Demonstrations in Africa - Afa'anwi Ma'abo Che (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2020)
Join Dr. Che as he explores the effects of Chinese official finance on state repression and public demonstrations in Africa. After using standard multiple regression analysis to measure how different attributes of Chinese and traditional official finance predict variations in rates of repression and demonstrations, Che looks at specific case studies in Cameroon and Uganda to illustrate his findings. These research findings have policy implications scholars, journalists, and policy practitioners need to keep in mind moving forward.
Keywords: 330